Security, strategy, and military dynamics in the South China Sea cross-national perspectives - Houlden, Gordon; Romaniuk, Scott Nicholas 1979-; Hong, Nong (Bristol University Press, 2021)
This volume brings together international experts to provide fresh perspectives on geopolitical concerns in the South China Sea. The book considers the interests and security strategies of each of the nations with a claim to ownership and jurisdiction in the Sea. Examining contexts including the regioń€™s natural resources and Chiná€™s behaviour, the book also assesses the motivations and approaches of other states in Asia and further afield. This is an accessible, even-handed and comprehensive examination of current and future rivalries and challenges in one of the most strategically important and militarized maritime regions of the world
Title from publisher's bibliographic system (viewed on 13 Apr 2023)
Strategic challenges and escalating power rivalry in the South China Sea - Scott N. Romaniuk and Nong Hong -- - 1 - Between competition and war: complex security overlay and the South China Sea - Joshua Hastey and Scott N. Romaniuk -- - 2 - The South China Sea as an echo chamber of Chinese foreign and security policy - Scott N. Romaniuk and Tobias Burgers -- - Part I - Claimants of the contested South China Sea -- - 3 - China's security interests and strategies in the South China Sea - Li Yang -- - 4 - Taiwan's South China Sea policy under the Tsai Administration - Yann-Huei Song -- - 5 - Vietnam and the East Sea in its strategic thinking - Đõ̂ Thanh Hải and Nguyẽ̂n Thị Linh -- - 6 - The Philippines and the South China Sea Dispute: Duterte's hedging approach with China and the United States - Rommel C. Banlaoi -- - 7 - Competition, contention and cooperation in the South China Sea: the Malaysian perspective - Sumathy Permal -- - Part II
- Non-claimants in Southeast Asia -- - 8 - A wary warrior: Indonesia's "soft-assertiveness" in the South China Sea - Senia Febrica and Scott N. Romaniuk -- - 9 - The South China Sea Dispute: regional integration, Status Ad Quem and Singapore's position - Hui-Yi Katherine Tseng -- - 10 - Cambodia's South China Sea policy: from ASEAN aligned to echoing Chinese clientism - Veasna Var -- - 11 - ASEAN's involvement in the South China Sea Disputes: the economics-security conundrum - Mingjiang Li and Yinghui Lee -- - Part III - Quadrilateral security dialogue states -- - 12 - The United States and the South China Sea question - John Callahan -- - 13 - Japan's security interests and strategies in the South China Sea - Masafumi Iida -- - 14 - Australia's geopolitics and the South China Sea - Leszek Buszynski -- - 15 - India and the South China Sea crucible : "cautious inclinations of an extra-regional "leading power" - Sourabh Gupta -- - Part IV
- Non-claimants in Europe and Eurasia -- - 16 - Britain's pivot to Asia: the big picture - Ian Park and Kun-Chin Lin -- - 17 - Balancing and hedging: the two levels of Russia's behaviour in the South China Sea - Alexander Korolev -- - 18 - South Korea and the South China Sea : a middle-power model for practical policies? - Sukjoon Yoon -- - Conclusion - Looking over the horizon - prospects for settlement of the South China Sea dispute? - Gordon Houlden
Keywords: Jurisdiction, Territorial / South China Sea; Sea-power / South China Sea; Maritime boundaries / South China Sea; Sicherheitspolitik; South China Sea / International status; South China Sea Region / Relations; Südchinesisches Meer; Aufsatzsammlung